Correction: Han et al. Research and Application of Information Model of a Lithium Ion Battery Intelligent Manufacturing Workshop Based on OPC UA. Batteries 2020, 6, 52 - Youjun Han; Yueming Hu; Yaqing Wang; Gang Jia; Chengjie Ge; Chunjie Zhang; Xuejie Huang (Batteries, 2023)
The authors wish to make the following corrections in Section 3 [...]